Ozone-based Advanced Oxidation Process for pharmaceutical contamination in wastewater: A review - Pratiwi Wahyu Zuli; Hadiyanto Hadiyanto; Widayat Widayat (E3S Web of Conferences)
Pharmaceutical contaminants, categorized as a subset of Emerging Contaminants, primarily originate from pharmaceutical industries and hospital activities. These pollutants pose significant environmental and public health risks due to their bioactive nature and widespread presence in various ecosystems. Their complex composition in wastewater and low concentrations present a global challenge, as conventional treatment methods often need to be more effective. Advanced oxidation processes (AOPs) have emerged as a promising solution, offering high oxidation efficiency and facilitating the mineralization of such micropollutants. Among various AOPs, ozone-based AOPs stand out because radical hydroxyl is produced with high reactivity. This makes it particularly effective for degrading pharmaceutical micropollutants like antibiotics, which are known for their pseudo-persistent behaviour in the environment. Furthermore, integrating ozone-based AOPs with biological treatments provides a synergistic approach to wastewater treatment, enhancing degradation efficiency while reducing the formation of toxic by-products. This integration can be implemented as a pre-treatment or a post-treatment step, tailoring the process for optimal pollutant removal. This review explores the mechanisms and applications of ozone-based AOPs, focusing on their potential to mitigate pharmaceutical contaminants in wastewater.